Computational study on shear strengthening of RC continuous beams using CFRP sheet - Alnatit, Nabil Mohamed Emhdab (2011)
This research studied the feasibility and effectiveness of a new method of strengthening existing RC continuous beams in shear by using CFRP strips. The CFRP composite strips were used to strengthen concrete externally at a known failure plane to resist shear stresses in shear friction. All beams were design to fails in shear with av/d 2.5. This research describes the computational study on shear strengthening of RC continuous beams using CFRP strips. In this study, a computational program consisting of 5 beams were performed subjected to experimental program with the same size and details of the beams where the experimental study was performed by other student in the laboratory. Here in this part the study done through simulation by ABAQUS Software version 6.9. Therefore, this research aims to investigate the effectiveness of using externally bonded CFRP strips in repair and strengthen of RC continuous beams and also to know the behavior of RC continuous beams strengthened in shear with CFRP sheet. So in this study there are five specimens with different CFRP wrapping scheme as 90 degree and 45 degree with three sides and four sides each beam. The computational results were compare with the experimental results that obtained by other student. The computational results show great agreement with the experimental results.